مراسيم الجنائز في المغرب الإسلامي خلال القرنين (4 ــ 9ه/10 ــ 15م - تريكي,اعمارة; غانية,بشير (University of Eloued جامعة الوادي, 2023)
يهدف هذا البحث إلى دراسة القيم والممارسات المرتبطة بظاهرة الموت من خلال تعاليم الشرع والعادات والأعراف التي مارسها سكان المغرب الإسلامي والتي عبّرت بدقة عن إيمان الفرد المغربي بهاته الظاهرة إيمانا قاطعا وأمرا حتميا، وقد ركّزنا على مراسيم الجنائز كونها حيّز يستلزم تطبيق الشرع فيه، ولهذا ارتأينا أن نسلّط الضوء على أهم الطقوس والشعائر المتبعة في تشييع الجنائز منذ الإعلان عن الوفاة حتى آخر طقس جنائزي. Abstract: The research aims to study the values and phenomenon through sharia rules, habits and traditions which were practiced by the inhabitan of Islamic Maghreb. these charia rules habits and tradition deeply expressed he foith of Maghrebien individual of this phenomenon.we had focused on funeral ceremonics in which it is a spacerequires applicating sharia.so we had seen that we have to highlight the most important ceremonies which are followed in funerals since the announcement of the deathe until the last funeral ceremony
Keywords: المغرب الإسلامي; Death; The funeral; Washing; Shrouding; Burial; Islamic Maghreb